Pengembangan Potensi Desa Kertonegoro melalui Program Gerabah oleh Mahasiswa KKN Kolaborasi 3 - Wahyudi, Kalvin Edo; Putri, Anggela Setiya; Rohizah, Siti; Wati, Ika Murni; Jehan , Devinna (Universitas Negeri Surabaya, 2025)
Some of the main problems experienced by pottery craftsmen include limited human resources or workers, as well as modernization. So preserving pottery crafts is not only about practice but also needs to involve education and increasing public awareness, especially the younger generation, regarding the importance of preserving cultural heritage. This becomes a benchmark for Collaborative KKN students to realize these achievements by conducting observations as an initial stage to directly observe the implementation, activities of the manufacturing process as well as observing the tools and materials needed to make pottery. So that later data will be obtained and conclusions can be drawn from the results of the observations that have been made. Next, they carried out pottery making practices involving student participants in the hope that they would be able to recognize the heritage that must be preserved and encourage them to think creatively and innovatively. Apart from cultural factors, the development of this pottery is also to increase economic opportunities that can be developed by Kertonegoro residents.